Structural health monitoring of the church of Santa Casa da Misericórdia of Aveiro using FBG sensors - Lima, H.F.
This paper presents a structural health monitoring system, based on fibre Bragg gratings, developed for the church of Santa Casa da Misericordia of Aveiro. This system comprises 19 displacement sensors and 5 temperature sensors. All the sensors were custom made according to the monitoring points’ characteristics. The results obtained over the first months are presented. The objective of this work is to gather data that will bring a deeper knowledge of how this structure behaves and to help planning the recovering interventions in this historical building.